1958
DOI: 10.1172/jci103669
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of the Urinary Cortisolc Metabolites, “Tetrahydro F,” “Allo-Tetrahydro F” and “Tetrahydro E”: Effects of Adrenocorticotropin and Complex Trauma in the Human1

Abstract: Methods for the quantitative estimation of plasma cortisol concentration have been devised by Nelson and Samuels (1), Silber and Porter (2), and Peterson and Wyngaarden (3) who used the sulfuric acid-induced fluorescence developed by Sweat (4). Together with urinary procedures (5, 6) these techniques have been employed to determine the secretion of cortisol by the adrenal in normal and pathological conditions (7-9) and to evaluate the factors involved in the "removal" of cortisol from the plasma in surgery (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

1959
1959
1974
1974

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Only 2 to 4 per cent of the total THF, allo-THF, and THE excreted is represented by allo-THF in both the control and post-operative periods. This is in marked contrast to the 15 to 30 per cent proportion of allo-THF reported for normal adults (8,9,12,25).…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…Only 2 to 4 per cent of the total THF, allo-THF, and THE excreted is represented by allo-THF in both the control and post-operative periods. This is in marked contrast to the 15 to 30 per cent proportion of allo-THF reported for normal adults (8,9,12,25).…”
Section: Resultscontrasting
confidence: 81%
“…In Table I, f, the ratios of THF: THE, 3.1 in the post-operative and 2.1 in the control period, are both highly elevated when compared with the values (2 1.0) in normal adults (8,9,12,25) and those (approximately 1.0) in adults stimulated with ACTH (11,12,26). The higher value of the THF: THE ratio in the post-operative as compared with the control period of Table I is consistent with previous findings (12) that a variety of "stress" situations, surgery included, produce elevations in the THF: THE ratio and that this phenomenon involves alterations in the metabolism of cortisol.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition almost complete absence of allo-THF was observed in a chronically ill individual and it reappeared upon convalescence. The rate of secretion of cortisol was one factor involved in producing the increase in urinary THF: THE, since following the administration of adrenocorticotropin (ACTH) to normal individuals the relative proportion of urinary THF as compared with THE was observed to rise (1)(2)(3)(4)(5) factors other than the rate of adrenal secretion were involved in altering the rates of excretion of the numerous metabolites of cortisol. It became clear that knowledge concerning the pathways of metabolism, the pool sizes of the metabolites and the relative rates of formation of the individual metabolites from cortisol would prove valuable in interpreting the urinary excretion patterns of these compounds.2 Consequently these studies were undertaken to determine the extent of the reaction THF = THE in volunteer subjects with and without the administration of ACTH; the pathways for the formation of THF, allo-THF, THE and cortolone from cortisol; the miscible pool size of THF, allo-THF, THE and cortolone; and the possibility of determining the overall rates of formation of THF, allo-THF and THE.…”
mentioning
confidence: 99%
“…(Submitted for publication July 23, 1959; accepted August 31, 1959) Variations have been shown to occur in the quantitative urinary excretion pattern of the metabolites of cortisol in a variety of traumatic events such as surgery, bone fracture and burns (1). The compounds evaluated were THF, allo-THF and THE,' and it was demonstrated that the relative proportion of THF: THE excreted during and after a "traumatic event" was markedly increased.…”
mentioning
confidence: 99%